Independent Learning Curriculum in Creative Products and Entrepreneurship Subjects in Vocational High Schools - Tonich; Sundari; Sri Rohaetin; Eriawaty (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2024)
Creative Products and Entrepreneurship (PKK) is designated as a subject with five lesson hours per week, taught by all general subject teachers, so in practice this subject is used for uncertified teachers to obtain certification. This risks lowering the quality of teaching if teachers' main focus is on certification rather than improving students' competencies. This research aims to comprehensively analyze the implementation of the PKK independent learning curriculum. This type of research uses a field research method with a qualitative approach. The research informants were six PKK subject teachers. Data collection procedures through observation, interviews, and documentation. The data analysis technique uses qualitative descriptive analysis. The results showed that the implementation of Merdeka Belajar Curriculum has been carried out in stages, including the preparation of teaching modules, teaching materials, learning tools, evaluations, and reports on student learning outcomes. The preparation of PKK teaching modules has also been carried out with supervision from the school and the Education Office. The implications of this study indicate that the implementation of Merdeka Belajar Curriculum has been carried out systematically, but still faces challenges. The research results can be the basis for policy makers to provide further support, such as providing training for teachers in preparing teaching modules, improving IT skills, and fulfilling facilities and infrastructure. The routine evaluations carried out can be further developed to increase the effectiveness of learning and ensure the achievement of student competencies according to curriculum objectives.